Development of a Medication Compliance Determinant Instrument for Low-Middle Literate Patients with Type 2 Diabetes Mellitus - Panduwiguna, Ivans; Sauriasari, Rani; Sartika, Ratu Ayu Dewi; Riyadina, Woro; Renaldi, Fransiskus Samuel (Kesmas, 2023)
Diabetes, a leading cause of 6.7 million deaths in 2021, poses a significant challenge despite existing interventions. Non-adherence to treatment remains a barrier to diabetes management. However, a comprehensive instrument to assess medication adherence determinants in diabetes patients’ population in Indonesia with low-medium literacy levels and following the sociocultural characteristics of Indonesian society has been lacking. This study aimed to develop and evaluate a valid and reliable instrument for measuring medication adherence in type 2 diabetes mellitus patients based on the Borg and Gall model. Through the input of an expert panel, a valid and reliable instrument was developed, which comprised 21 questions and encompassed all medication adherence determinants, with a CVR and CVI value of 1 and a final Cronbach’s alpha value of 0.731. This instrument is still being tested and needs to be implemented in the right and wider population to obtain more accurate results.